Upaya Meningkatkan Hasil Belajar Siswa Dengan Menggunakan Alat Peraga Balok Dan Kubus Pada Mata Pelajaran Matematika Tentang Bangun Datar di Kelas IV SD - Tang, Afifah Annadia; Noviyani, Rafiqa (Yayasan Rahmat Islamiyah, 2024)
This research aims to explore efforts to improve student learning outcomes in mathematics subjects about plane figures in class IV elementary school through the use of teaching aids in the form of blocks and cubes. The experimental method was used involving two groups of students: a control group that did not use props and a treatment group that used props. Data was collected through tests before and after treatment to assess improvements in learning outcomes. The results showed that the use of block and cube props significantly increased students' understanding of flat shapes. The implications of this research suggest the importance of integrating teaching aids in mathematics learning in elementary schools to improve student understanding of concepts and learning outcomes.